Catechisms for children and young people in the years 1945–1949 - Lewandowicz-Nosal, Grażyna (Folia Toruniensia, 2017)
The article discusses catechisms for children and youth published in Poland in the years 1945-1949. The bibliography includes 58 catechisms. What is a characteristic feature of the genre is its visible standardization, adaptations and shortened versions. Catechisms were written by priests. Most of them were published in 1949. The most significant publishers were diocesan curias in Katowice, Kielce, Olsztyn, monastic and secular publishing houses. The presented material was examined on the basis of the copies preserved in the National Library. The collection was divided into the following sub-sections: 1. Catechisms preparing to the first confession and communion, 2. General/shortened catechisms, 3. Catechisms for the youth.